2000
DOI: 10.1017/s1047951100009719
|View full text |Cite
|
Sign up to set email alerts
|

Arrangement of the systemic and pulmonary venous components of the atrial chambers in hearts with isomeric atrial appendages

Abstract: The postero-superior walls of the atrial chambers in hearts with isomeric atrial appendages can be analysed on the basis of a compound structure made of bilateral systemic venous components, a central pulmonary venous component, and the body of the atrium. Hearts with isomeric right appendages have absence or hypoplasia of the pulmonary venous component, while hearts with isomeric left appendages have hypoplastic systemic venous components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 17 publications
0
31
0
2
Order By: Relevance
“…Abnormal LR cardiomyocyte compositions were frequently associated with CHDs, which suggests that the ability of different regions of the heart to become differentiated into particular structures is linked to cardiac cell lineage. For example, the left and right atria derive from a common progenitor, the common atrium, which must become divided into two chambers with distinct LR differences (Anderson, 1992;Markwald et al, 1998;Min et al, 2000). LR labeling of the primary heart fields previously suggested that this division is related to the LR origin of cells that contribute to this region (Gormley and Nascone-Yoder, 2003).…”
Section: Research Articlementioning
confidence: 99%
“…Abnormal LR cardiomyocyte compositions were frequently associated with CHDs, which suggests that the ability of different regions of the heart to become differentiated into particular structures is linked to cardiac cell lineage. For example, the left and right atria derive from a common progenitor, the common atrium, which must become divided into two chambers with distinct LR differences (Anderson, 1992;Markwald et al, 1998;Min et al, 2000). LR labeling of the primary heart fields previously suggested that this division is related to the LR origin of cells that contribute to this region (Gormley and Nascone-Yoder, 2003).…”
Section: Research Articlementioning
confidence: 99%
“…2A-D). Such features are typically found in human hearts with left cardiac isomerism as well as in mouse models for this subset of the visceral heterotaxy syndrome [18][19][20].…”
Section: Discussionmentioning
confidence: 97%
“…This diagnosis is furthermore supported by the fact that the abnormal embryonic chick heart had striking hypoplasia of its systemic venous component (sinus venosus) in combination with anomalous pulmonary venous drainage to the right-sided atrium (Figure 2A-D). Such features are typically found in human hearts with left cardiac isomerism as well as in mouse models for this subset of the visceral heterotaxy syndrome [18][19][20]. Previous data from mice disclosed a correlation between the isomeric expression of Pitx2 and the occurrence of the double outlet from the right ventricle (DORV) [11].…”
Section: Discussionmentioning
confidence: 98%